1988
DOI: 10.1111/j.2044-835x.1988.tb01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between blood lead, behaviour, psychometric and neuropsychological test performance in young children

Abstract: A sample of 201 inner city dwelling children age 5.5 years was assessed on a wide variety of cognitive, performance, neuropsychological and behavioural measures. Extensive sociodemographic and family indices were also assessed. Body burden of lead was derived from a venous sample of blood. Data were analysed using both univariate and multivariate techniques. Results show that the initial correlations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Harvey et al (1988) found no significant correlation between PbB Meta-analyses. Needleman and Gatsonis (1990) did a meta-analysis of 12 studies, 7 of which used blood lead as a measure of exposure and 5 used tooth lead.…”
Section: Health Effectsmentioning
confidence: 91%
“…Harvey et al (1988) found no significant correlation between PbB Meta-analyses. Needleman and Gatsonis (1990) did a meta-analysis of 12 studies, 7 of which used blood lead as a measure of exposure and 5 used tooth lead.…”
Section: Health Effectsmentioning
confidence: 91%
“…However, the results of different studies do not agree. Of the four most recent and methodologically sound studies carried out in the UK, three [23][24][25] showed no evidence to support the view that low-level lead exposure is associated with IQ deficits and one [26] identified a relationship between blood lead and a measure of attentional processes, which appeared to be an important component of the child's overall ability score. In these four studies lead levels were relatively low and typical of those of children living in inner city areas in the UK.…”
Section: Current Evidencementioning
confidence: 99%
“…Schroeder [29] has also drawn attention to the important effects of the quality of the care-giving environment in the home on both lead levels and IQ. In studies where the design and selected popula tion allow these factors to be taken into account, there is some evidence of a greater effect of low-level lead expo sure in children of lower SES [30,31], although not all investigators agree [25,32],…”
Section: How the Effect Is Determinedmentioning
confidence: 99%